PENGARUH BIBLIOTERAPI TERHADAP PENURUNAN KECEMASAN ANAK YANG MENJALANI HOSPITALISASI DI RS BHAYANGKARA DENPASAR - Ni Made Dwi Arsita Wati; I Made Dwie Pradnya Susila; Ni Komang Purwaningsih (Journal of Advanced Nursing and Health Sciences, 2021)
Hospitalization is a process of planning or emergency reasons that require children to be hospitalized for therapy. Being hospitalized is a big problem and creates fear and anxiety for the children. One of the efforts to overcome anxiety is by doing bibliotherapy. Doing bibliotherapy will provide many benefits, namely reducing stress or pressure faced, in terms of emotion bibliotherapy can help restore the condition of individuals who have trauma, eliminate boredom experienced by someone, and also reduce tension in oneself. Reading is a distraction that can lower stressor hormones, activate natural endorphins, and divert attention from fear, anxiety and tension, improve the body's chemical system, lower blood pressure and slow down breathing, heart rate, pulse, and brain wave activity. The purpose of this study was to identify anxiety experienced by children undergoing hospitalization before and after performing bibliotherapy and to analyze the effect of bibliotherapy on reducing anxiety in children underwent hospitalization.The research design used was pre experimental one-group pretest-posttest. This research was conducted at Bhayangkara Denpasar Hospital in December 2020. The number of respondents in this study was 37 respondents who were determined using non-probability sampling, namely purposive sampling. Respondents performed bibliotherapy every day for 45 minutes. The analysis used the Wilcoxon test to determine the effect of bibliotherapy on reducing anxiety of children undergoing hospitalization.The results of the bivariate analysis used the Wilcoxon test and the p value was 0,000 because the p value <α (0.05), then H0 was rejected. This means that there was an effect of bibliotherapy on decreasing anxiety of children undergoing hospitalization at Bhayangkara Hospital in 2021.